Upaya Mengoptimalkan Perkembangan Anak Usia Dini (THUFULA, 2014)
early childhood cognitive development is still in the pre-operationalenvironmental needs help to stimulate and provide an opportunity to growand develop optimally. That all human beings have the potential to developoptimally, it takes the efforts of the external environment as well as the spirit ofthe internal factors (by understanding the strengths and weaknesses) to meetthe personal needs and social demands. So they fully develop human being toface the competition in the next phase (teens, adults, parents, and the elderly).Due to the success of the development at an early age will determine the successof subsequent developments.